Dermatoscopy of Cutaneous Lichen Planus - Attempt to Translate Metaphoric Terminology Into Descriptive Terminology - Agata Szykut-Badaczewska; Mariusz Sikora; Lidia Rudnicka; Harald Kittler (Mattioli1885, 2023)
Introduction: Dermatoscopy is gaining appreciation in assisting the diagnosis of inflammatory dermatoses (inflammoscopy). Lichen planus (LP) is a common inflammatory skin disease with characteristic dermatoscopic features. Objectives: The objective of this study was to review the literature on the dermatoscopy of lichen planus and to re-evaluate the published descriptions in the light of the 2019 expert consensus on the terminology of dermatoscopy for non-neoplastic skin diseases. Methods: We searched the PubMed database using the keywords 'lichen planus and dermatoscopy', 'lichen planus and dermoscopy', 'lichen planus and epiluminescence microscopy', and 'lichen planus and inflammoscopy'. Results: Of 413 articles retrieved, we selected 67 articles for full-text review, and finally included 63 articles, mostly case reports or small case series, comprising 572 patients with lichen planus. We identified 113 different terms or short descriptions that were used to characterize the dermatoscopy of lichen planus. Frequently, authors applied various terms to variants of the same feature. Although reported under different designations, Wickham striae were the most consistent dermatoscopic feature of lichen planus. Other characteristics of lichen planus, such as vascular patterns, pigmented structures, and follicular findings were less consistent or depended on skin type, anatomic site, disease stage, and applied treatment. Conclusions: While Wickham striae are the single most important clue for diagnosis, other dermatoscopic characteristics of lichen planus are less consistent. Based on descriptions published in the literature we established a dictionary of useful terms for the description of lichen planus that is consistent with the terminology suggested by the recent consensus conference.